Revitalisasi Ekonomi Kreatif dan Pertanian Berkelanjutan di Desa Bayasari - Arif Arif; Munawar Fauzan Irhamna; Naila Agisti; Nabila Wanda Dwi Putri; Nyimas Sania Farha Syakira; Puput Nurlaila; Nina Ramdani; Milah Nurmilah; Changnara Novita Syahri; Hilman Amarudin; Galang Riarulhaq; Lutpi Sahri Ramdani; Winda Nurazizah; Muhammad Rizky Nugraha; Fathasya Aulia Maharani (Universitas Perjuangan Tasikmalaya, 2026)
This comprehensive community service program was designed to address the multidimensional challenges faced by farmers and micro-enterprise actors in Bayasari Village, Ciamis Regency, with main focus on digital marketing limitations and financial literacy gaps. Through a participatory action research approach, the program implemented a series of integrated interventions covering six development sectors simultaneously: education, health, economy, environment, institutional development, and disaster mitigation. Methodologies consistently applied throughout the program included participatory rural appraisal for problem mapping, focused group discussions for solution formulation, hands-on practical training for capacity building, and continuous mentoring to ensure knowledge adoption. The achieved results showed significant success with improved digital capacity among 32 core participants, where 85% successfully mastered online platform management independently. In addition to the main economic outcomes, the program also successfully generated positive impacts in supporting sectors, including increased health awareness among elderly groups, strengthened environmental education in elementary education institutions, and enhanced institutional capacity through the development of an integrated village profile website. The successful implementation of this program empirically proves the importance of holistic and multi-sectoral approaches in building rural community resilience, while affirming the strategic value of multi-party collaboration between academics, village government, and communities in creating sustainable socio-economic transformation.